Occupational safety and health in logging operations at Ondo State afforestation project (2011)
Assessment of the various types of hazard exposed to by logging crews in a Nigerian Forest Reserve was carried in this stud y . The study site was the Ondo State Afforestation Project (OGAP) South West Nigeria. Data collection involved the use of ergonomic checklist, participatory approach, on-the-spot assessment and oral interviews. Data collected were subjected to statistical analysis. The results showed that the commonest hazards exposed to by log felling crews were vibrations, noise, stress and mental workload. Accident rate during felling was very low as 10% of the workers claimed to have being involved in logging accidents during log loading recorded the highest frequency. All the crew members were exposed to a long duration (about 6hrs) of intense noise daily but only 30% could note the effect of noise on their health while 20% reported the effect of noise on their efficiency. None of the crew members has ever gone for audiometry test in the last five years. Fifty five percent of the worker were exposed to vibrations, of these, 30% are exposed to whole body vibration, 10% to hand-arm vibration while 15% were exposed to both hand-arm and whole body vibration. The affected workers reported on the negative effect of vibration on their health. A standard working time was observed, but slight variation still exist as break time were not being observed in the study area. Although there is provision of safety rule and protective gadgets, the workers were not using them as they claimed that it could affect their safety and efficiency. Workers carelessness, ignorance and lack of proper training and not adhering to the instruction manuals were some of the factors responsible for the high rate of hazard on the job.